A global population genomic analysis shows novel insights into the genetic characteristics of endometriosis. (2023) - PAPAGEORGIOU, LOUIS; ANDREOU, ATHENA; ZERVOU, MARIA; VLACHAKIS, DIMITRIOS; GOULIELMOS, GEORGE N.; ELIOPOULOS, ELIAS
No abstract available